SuperAging: A model for studying mechanisms of resilience and resistance: Reserve and resilience: Opportunities and mechanisms for dementia prevention. (7th December 2020) - Rogalski, Emily J; Sridhar, Jaiashre; Martersteck, Adam; Makowski‐Woidan, Beth; Engelmeyer, Janessa; Parrish, Todd; Besson, Pierre; Cobia, Derin; Paxton, Holly; Weintraub, Sandra; Katsaggelos, Aggelos; Bandt, Katie; et al.
Abstract: Background: Memory complaints are widespread among the elderly and aging is a major risk factor for Alzheimer's disease (AD), leading to the impression that gradual loss of memory ability is a nearly universal consequence of getting old. Our longitudinal studies of SuperAgers, 80+ year‐olds with episodic memory performance that remains in the range that is at least normal for 50‐60 year‐olds suggests an alternative aging trajectory is possible. This session will highlight some of the emerging biologic features of the SuperAgers. Method: Participants include SuperAgers and cognitively average 80+ year‐old cognitively average normal controls. Data from detailed neuropsychological assessments, quantitative neuroimaging measurements (MR and amyloid PET), genetic features and neuropathologic findings will be reported. Result: Initial evidence suggest SuperAgers tend to show mismatch between chronologic and biologic age, including maintenance of cortical but not necessarily hippocampal volume, a tendency to resist significant amyloid PET retention, an abundance of anterior cingulate Von Economo neurons, and some with resistance to cortical Alzheimer's pathology. Conclusion: These studies contribute to our understanding mechanisms of resilience and resistance in cognitive aging and may help isolate factors that are potentially important for promoting successful cognitive aging and avoiding age‐related brain diseases such as AD.